Prevalence of thyroid dysfunction and its effects on fetomaternal outcome in pregnant women of Eastern Uttar Pradesh, India - Kumari, Ankita; Srivastav, Reena; Mitra, Shaila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of the study is to determine the prevalence of thyroid dysfunction in pregnancy and its impact on obstetrical outcome in Eastern Uttar Pradesh. Methods: This was a prospective observational study undertaken at antenatal clinics and indoor of BRD Medical College, Gorakhpur. Total 720 antenatal women, ≤20 weeks of gestation were recruited for the study. In all patients’ routine obstetrical investigations and thyroid function tests were done. All patients were followed up to delivery. Maternal and perinatal outcome were ascertained. Results: Prevalence of thyroid dysfunction among pregnant was found to be 21.1% and subclinical hypothyroidism (15.9%) was the commonest thyroid disorder. Most common complication observed in subclinical and overt hypothyroidism was preeclampsia (9.56 % versus 20%) followed by preterm labour (7.82% versus 10%). Major fetal complications in hypothyroid mothers included intrauterine growth restriction, low birth weight and stillbirth. Conclusions: Prevalence of hypothyroidism was found to be high in our study and was associated with adverse pregnancy outcomes; hence, thyroid screening should be included in routine antenatal investigations.